Narcissistic Personality Disorder: Possible Effects on the Validity of Marrital Consent - Sanson, Robert (Monitor ecclesiasticus, 1989)
Der Autor beschreibt die Strukturelemente des Narzismus im Hinblick auf die Ehenichtigkeitsklage gemäß can. 1095.3